Atomic Force and Optical Microscopy Characterization of the Deformation of Individual Carbon Nanotubes and Nanofibers. (14th February 2008) - Bigioni, Terry P.; Cruden, Brett A.
Abstract : A popular technique for characterizing the mechanical properties of carbon nanotubes is to apply a one-dimension axial compression and measure its response to the compressive force. At some critical compression, a dramatic decrease in the force is observed. This has previously been attributed to Euler buckling, allowing the elastic modulus to be calculated from the Euler buckling force. We have attached individual plasma enhanced chemical vapor deposition (PECVD) grown carbon nanofibers (CNFs) and thermal chemical vapor deposition (CVD) grown carbon nanotubes (CNTs) to the apex of an atomic force microscope (AFM) cantilever to examine this mechanical response. By combining the force measurements and simultaneous video microscopy, we are able to observe the mechanical deformation and correlate points in the force curve with phenomena such as slipping and bending. Analysis of the mechanical response must therefore be interpreted in terms of bending and/or slipping of a tube compressed by an off-normal force.